Better Algorithms through Faster Math: The search for new algorithms that could reduce the time needed for multiplication is now at the center of data science. - Greengard, Samuel (Communications of the ACM, 2023)
The article focuses on the search for algorithms that can reduce the time needed for multiplication problems within the fields of machine learning (ML), deep learning (DL), and artificial intelligence (AI). Topics discussed include the history of matrix multiplication and the data science group DeepMind and their ML approach AlphaTensor.